2007
DOI: 10.1128/aac.00893-07
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nucleoside Reverse Transcriptase Inhibitors on Mitochondria in Human Immunodeficiency Virus Type 1-Infected Children Receiving Highly Active Antiretroviral Therapy

Abstract: Mitochondrial toxicity induced by nucleoside reverse transcriptase inhibitors (NRTIs) has been reported to be responsible for various adverse effects. The relative impact of NRTIs on the mitochondria of human immunodeficiency virus (HIV) type 1 (HIV-1)-infected children receiving highly active antiretroviral therapy (HAART) is unknown. Mitochondrial DNA (mtDNA) levels were quantified longitudinally from peripheral blood mononuclear cells (PBMCs) in 31 HIV-1-infected children from Pediatric AIDS Clinical Trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 49 publications
4
34
0
Order By: Relevance
“…In agreement with our previous in vivo data (30), mtDNA significantly increased in myoblasts treated with AZT-containing regimens. Similar findings are also observed in other in vitro models, including human hepatoblastoma (HepG2) cells (5) and HSMCs (2).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with our previous in vivo data (30), mtDNA significantly increased in myoblasts treated with AZT-containing regimens. Similar findings are also observed in other in vitro models, including human hepatoblastoma (HepG2) cells (5) and HSMCs (2).…”
Section: Discussionsupporting
confidence: 82%
“…We previously reported that 2Ј,3Ј-dideoxyinosine (didanosine, or ddI) significantly altered mtDNA in peripheral blood mononuclear cells (PBMCs) of HIV-1-infected children who had undetectable plasma HIV-1 RNA for more than 2 years while receiving HAART (30). This is particularly important for children, who are potentially more vulnerable than adults to the adverse effects of antiretrovirals because of their long-term exposure and the possible negative impact on growth and development (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The initial increase may be an attempt to compensate for mitochondrial stress or dysfunction, which may also explain some of the discrepancies in the NRTI mitochondrial toxicity literature with respect to adult HIV populations, for which results have been mixed [40]. Although studies of long-term NRTI exposure in therapy-experienced patients tend to show decreased blood cell mtDNA levels [33,41,42], initial increases in blood cell mtDNA level have been observed in d4T-naive adults initiating HAART [43] and in children switching to ZDV-containing HAART [44]. It has also been suggested that early increases in mtDNA may represent a restorative phenomenon, countering the mtDNAdecreasing effect of HIV itself [43].…”
Section: Discussionmentioning
confidence: 95%
“…[5][6][7][8][9][10] Studies have also shown an association between ARVs and mitochondrial abnormalities in HIVinfected children. 11,12 Little is known, however, regarding mitochondrial alterations in HIV-infected children with clinical evidence of insulin resistance or other metabolic complications, and whether these changes can be attributed to ARVassociated mitochondrial toxicity.…”
mentioning
confidence: 99%